Exploiting the Anti-Aggregation of Gold Nanostars for Rapid Detection of Hand, Foot, and Mouth Disease Causing Enterovirus 71 Using Surface-Enhanced Raman Spectroscopy - Reyes, Miguel (AMER CHEMICAL SOC, 2020)
10.1021/acs.analchem.7b00066